[Book of abstracts] Fuel Cells Science & Technology 2010, World Trade Centre, Zaragoza, Spain, 6-7 October 2010 (Zaragoza, Spain : s.n., 2010)
Provides abstracts for the paper presented in Fuel Cells Science & Technology Conference 2010, World Trade Centre, Zaragoza, Spain, 6-7 October 2010. Searching can be made through title index, subject index and author index
System requirements: Data view using internet navigator and software by Oxford Abstracts
Keywords: Fuel cells